2018
DOI: 10.1155/2018/6254308
|View full text |Cite
|
Sign up to set email alerts
|

Targeting YOD1 by RNA Interference Inhibits Proliferation and Migration of Human Oral Keratinocytes through Transforming Growth Factor-β3 Signaling Pathway

Abstract: Objective We have identified a gene YOD1 encoding deubiquitinating enzyme (DUB) responsible for nonsyndromic cleft lip with or without cleft palate (NSCL/P). We aimed to determine the effects of YOD1 RNA interference (RNAi) on cell proliferation and migration, playing an important role in lip and palate formation, and to clarify whether the mechanisms involved TGF-β3 signaling associated with NSCL/P. Methods RNAi was applied to construct vectors expressing YOD1 small interference RNAs (siRNAs). The vectors wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Previous studies suggested that YOD1 correlated with another congenital malformed disease: nonsyndromic cleft lip, with or without cleft palate (NSCL/P). RNA interference and overexpression experiments indicated that YOD1 could enhance cell migration during lip and palate formation through the transforming growth factor (TGF)-β3 signaling pathway ( Zhou et al, 2018 ). A mutation of YOD1 may lead to impeded cell migration resulting in NSCL/P ( Ju et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that YOD1 correlated with another congenital malformed disease: nonsyndromic cleft lip, with or without cleft palate (NSCL/P). RNA interference and overexpression experiments indicated that YOD1 could enhance cell migration during lip and palate formation through the transforming growth factor (TGF)-β3 signaling pathway ( Zhou et al, 2018 ). A mutation of YOD1 may lead to impeded cell migration resulting in NSCL/P ( Ju et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the balance change between the above, TGF-β often changes from tumor suppression factor to tumor promotion factor during cancer progression [ 32 ]. Studies have reported that YOD1 RNAi in Human Oral Keratinocytes can inhibit cell proliferation and migration related to the pathogenesis of nonsyndromic cleft lip with or without cleft palate (NSCL/P) through TGF-β 3 signaling [ 33 ], which suggested that the targeted inhibition of YOD1 in the advanced stage of cancer may also play a role in inhibiting cell proliferation and migration. The above may be the key pathways that YOD1 promotes the occurrence and development of pancreatic cancer and affect the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…One precursor cell was HUC-MSCs, which can differentiate into chondrocytes ( Brown et al, 2019 ). Another mature cell line was HOK cells from oral mucosa, which was used to study the pathogenesis of NSCLP in previous studies ( Zhou et al, 2018 ; Li et al, 2020 ). The zebrafish palate consists of cells derived from the frontonasal and maxillary domain, which is similar to the palatogenesis of mammals ( Duncan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%